Exposure and Absorption of PAHs in Wildland Firefighters: A Field Study with Pilot Interventions. Issue 2 (23rd June 2020) - Cherry, Nicola; Galarneau, Jean-Michel; Kinniburgh, David; Quemerais, Bernadette; Tiu, Sylvia; Zhang, Xu
Abstract: Objectives: There is limited knowledge of exposure to polycyclic aromatic hydrocarbons (PAHs) in wildland firefighters, or of the effectiveness of interventions to reduce this. This study of wildland firefighters assessed whether PAHs were present and considered respiratory protection and enhanced skin hygiene as possible interventions. Methods: 1-Hydroxypyrene (1-HP) was measured in urine samples collected pre-shift, post-shift, and next morning from wildland firefighters in Alberta and British Columbia. Skin wipes, collected pre- and post-shift, were analysed for eight PAHs. Breathing zone air samples were analysed for 11 PAHs. As pilot interventions, participants were randomized to either normal or enhanced skin hygiene. A sample of volunteers was assigned to a disposable N95 mask or a half facepiece mask with P100 organic vapour cartridge. Participants completed a brief questionnaire on activities post-shift and respiratory symptoms. Results: Non-smoking firefighters (66 male and 20 female) were recruited from 11 fire crews. Air sampling pumps were carried for the full shift by 28 firefighters, 25 firefighters wore masks (14 N95 and 11 P100); 42 were assigned to the enhanced skin hygiene intervention. Sixty had hot spotting as their main task. Air monitoring identified PAHs (benzo( b, j, k )fluoranthene in particulates, phenanthrene in the gaseous phase) for 6 of the 11 crews. PAHs (largely naphthalene) were found post-shift on 40/84 skin wipes from the hand and 38/84 from jaw/throat. The mean increase in 1-HP in urine samples collected after the shift (compared with samples collected before the shift) was 66 ng g −1 creatinine ( P < 0.001) with an increase over the shift found for 76% of participants. 1-HP in next morning urine samples was significantly lower than at the end of shift (a reduction of 39.3 ng g −1 : P < 0.001). The amount of naphthalene on skin wipes was greater at the end of the shift (post) than at the start (pre). The mean post–pre weight difference of naphthalene on skin wipes taken from the hand was 0.96 ng wipe −1 ( P = 0.01) and from the jaw/throat 1.28 ng wipe −1 ( P = 0.002). The enhanced skin hygiene intervention lead to a larger reduction in 1-HP between end of shift and next morning urine samples but only for those with naphthalene on skin wipes at the end of shift. The difference in 1-HP concentration in urine samples collected before and after the shift was reduced for those wearing a mask (linear tend P = 0.063, one-sided). In multivariable models, 1-HP at end of shift was related to gaseous phase phenanthrene, estimated from air sampling [ β = 318.2, 95% confidence interval (CI) 67.1–569.2]. Naphthalene on hand skin wipes reflected work in hot spotting during the shift ( β = 0.53, 95% CI 0.22–0.86). Conclusions: This study provided evidence of PAHs in the air and on the skin of many, but not all, fire crew. Absorbed PAHs, reflected in 1-HP in urine, increased over the shift. Results from the pilot interventions suggest that enhanced skin hygiene would reduce absorption post fire where PAHs had been accumulated on the skin, and that masks could be effective in reducing PAH inhalation exposure. Interventions to reduce PAH absorption are supported by the pilot work reported here and warrant further evaluation across a full fire season.